2014
DOI: 10.1016/j.ymben.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A targeted proteomics toolkit for high-throughput absolute quantification of Escherichia coli proteins

Abstract: Transformation of engineered Escherichia coli into a robust microbial factory is contingent on precise control of metabolism. Yet, the throughput of omics technologies used to characterize cell components has lagged far behind our ability to engineer novel strains. To expand the utility of quantitative proteomics for metabolic engineering, we validated and optimized targeted proteomics methods for over 400 proteins from more than 20 major pathways in E. coli metabolism. Complementing these methods, we construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In E. coli, QconCAT was used for the absolute quantification of over 400 proteins from more than 20 major pathways in E. coli metabolism [17]. A study on Schistosoma mansoni carried out by Castro-Borges et al to evaluate amounts of previously identified tegument proteins using the QconCAT technique reported that aquaporin is the most abundant trans-membrane protein [18].…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, QconCAT was used for the absolute quantification of over 400 proteins from more than 20 major pathways in E. coli metabolism [17]. A study on Schistosoma mansoni carried out by Castro-Borges et al to evaluate amounts of previously identified tegument proteins using the QconCAT technique reported that aquaporin is the most abundant trans-membrane protein [18].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were analyzed using an AB Sciex (Foster City, CA) 5500Q-Trap mass spectrometer operating in MRM (SRM) mode coupled to an Agilent 1100 system. For method details, please see references (George et al, 2014) and (Batth et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore miniaturization of the LC system also influences the accuracy of several important LC characteristics including control of flowrate, solvent mixing and gradient formation. For this reason, often higher flowrates are chosen for targeted proteomic applications in which high reproducibility is required [55]. In addition higher flowrates have the advantage that ultrafast gradients (UPLC) can be used increasing sample throughput.…”
Section: ) Flowrate and Gradient Mixingmentioning
confidence: 99%